Taming the Wild Horse of Shadow Education The Global Expansion of Private Tutoring and Regulatory Responses - Zhang, Wei (Taylor & Francis, 2023)
Zhang analyses the phenomenon of private supplementary tutoring from a global perspective. The expansion of such tutoring alongside schooling is among the striking global shifts since the turn of the century. In many countries over half of the relevant cohorts of children receive private tutoring, with that proportion in some locations exceeding 80%. The sector has far-reaching implications for social inequalities, (in)efficiencies in educational processes, study burdens on students, family finances, innovation, and employment. Yet greatly-needed government regulations have typically been slow to catch up with the phenomenon. Commentary in the volume juxtaposes countries with strong regulations with counterparts having weak regulations. Conceptually, the book considers forces changing the roles of multiple stakeholders, including governments, entrepreneurs, teachers, families and students. A useful read for students and researchers interested in comparative education and governance.